Cold stress in rice (Oryza sativa L.): Molecular mechanisms of sensing, signaling, transcriptional regulation, membrane lipid remodeling, and hormonal modulation - Xiao, Peixiang; Xiong, Meixin; Hou, Kexin; Guo, Xueyan; Li, Hua; Liu, Yi (Frontiers in Plant Science, 2026)
Rice (Oryza sativa L.) is a staple crop. It was originally domesticated in tropical and subtropical regions, sustains nearly half of the global population and contributes approximately 20% of the world’s total dietary energy supply. However, its inherent sensitivity to low-temperature severely threatens yield stability. To meet the growing global food demand, rice cultivation is expanding to low-temperature-prone high-altitude and high-latitude regions. This expansion makes the low-temperature sensitivity problem worse. To cope with cold stress, rice has evolved a sophisticated regulatory network for cold sensing, signal transduction, and response. Recent research progress includes identifying key sensors (COLD1-RGA1, COG1-OsSERL2), characterizing secondary messengers (Ca²+, 2’,3’-cAMP, ROS) and downstream cascades (CBL-CIPK, CDPK, MAPK), elucidating core transcriptional modules (OsbHLH002/OsICE1-OsDREBs-COR) and auxiliary transcriptional factors (WRKY, MYB, NAC), uncovering critical genes involved in membrane lipid remodeling, and defining the roles of phytohormones (ABA and GA) that fine-tune cold stress responses. This review summarizes current understanding of these molecular mechanisms and highlights future directions for rice cold stress research.